Digital educational escape game design for STEM higher education - Gruber, Melissa; Faßbender, Stefanie (Frontiers in Education, 2025)
In higher education, lecturers experience difficulties motivating their students. Within the scope of this project, learning outcomes are intended to be enhanced by an innovative teaching and learning method: digital educational escape games. Exploring the design of digital escape games as a modern and constructivist approach to enhance teaching and learning in STEM (science, technology, engineering, mathematics) higher education, this paper outlines evidence-based research based on semi-structured expert interviews and qualitative content analysis. Experts’ insights into these thematic areas provide valuable perspectives on how digital escape games can effectively contribute to the teaching and learning experience in STEM disciplines. The results show expert opinions regarding key didactic aspects like the integration of educational content and learning processes into game design. It was found that the didactic and educational aspects of a game are inextricably linked and cannot be separated. In order to create an effective educational game, it is essential to establish the learning objective as the foundation for the game’s narrative. In addition to the consensus on the integration of didactics and games, there were also aspects on which educators and learners held opposing views. Hence, controversially discussed game design elements need to be subject of further research.